MXene‐Derived TinO2n−1 Quantum Dots Distributed on Porous Carbon Nanosheets for Stable and Long‐Life Li–S Batteries: Enhanced Polysulfide Mediation via Defect Engineering. Issue 21 (17th April 2021) - Zhang, Heng; Yang, Li; Zhang, Peigen; Lu, Chengjie; Sha, Dawei; Yan, Bingzhen; He, Wei; Zhou, Min; Zhang, Wei; Pan, Long; Sun, ZhengMing
Abstract: The application of Li–S batteries has been hindered by the shuttling behavior and sluggish reaction kinetics of polysulfides. Here an effective polysulfide immobilizer and catalytic promoter is developed by proposing oxygen‐vacancy‐rich Ti n O2 n −1 quantum dots (OV–T n QDs) decorated on porous carbon nanosheets (PCN), which are modulated using Ti3 C2 T x MXene as starting materials. The T n QDs not only confine polysulfides through strong chemisorption but also promote polysulfide conversion via redox‐active catalysis. The introduction of oxygen vacancies further boosts the immobilization and conversion of polysulfides by lowering the adsorption energy and shortening the bond lengths. The PCN provides a physical polysulfide confinement as well as a flexible substrate preventing OV–T n QDs from aggregation. Moreover, the two building blocks are conductive, thereby effectively improving the electron/charge transfer. Finally, the ultrasmall size of QDs along with the porous structure endows OV–T n QDs@PCN with large specific surface area and pore volume, affording adequate space for S loading and volume expansion. Therefore, the OV–T n QDs@PCN/S delivers a high S loading (79.1 wt%), good rate capability (672 mA h g −1 at 2 C), and excellent long‐term cyclability (88% capacity retention over 1000 cycles at 2 C). It also exhibits good Li + storage under high S‐mass loading and lean electrolyte. Abstract : A remarkable conversion kinetics‐enhanced polysulfide mediator is proposed via in situ preparation of oxygen‐vacancy‐rich Ti n O 2n− 1 quantum dots (OV–T n QDs) distributed on a porous carbon nanosheet (PCN) using 2D Ti3 C2 T x MXene as the starting material. The obtained OV–T n QDs@PCN/S cathode exhibits an ultrastable and long‐life Li + storage at high current density, demonstrating its great potential for next‐generation Li–S batteries.